Black women’s struggles for survival an anti-racist training - Clemente, Flávia da Silva; Lima, Tatiane Michele Melo de; Uchôa, Renata Pereira da Silva; Melo, Luanna Cássia dos Santos (Argumentum, 2024)
The article aims to present the survival and political resistance strategies of black women, members of two agroecological gardens in the metropolitan region of the cities of Olinda and Recife and their importance for anti-racist training. The research had intersectional and decolonial black feminism as its theoretical-methodological basis. We carried out participant observation and interviews with women, with popular education as the fundamental axis. The results indicate that racism is a significant social determinant that complicates struggles for survival. In Brazil, racism structures social relations, with black women needing to identify ways of overcoming the oppressive reality, turning collective and politically engaged actions into spaces for strengthening and training against oppression based on race, gender and social class.